Antibody persistence up to 5 years after vaccination of toddlers and children between 12 months and 10 years of age with a quadrivalent meningococcal ACWY-tetanus toxoid conjugate vaccine. Issue 1 (2nd January 2016) - Vesikari, Timo; Forsten, Aino; Bianco, Veronique; Van der Wielen, Marie; Miller, Jacqueline M
Abstract : We studied the persistence of serum bactericidal antibody using rabbit and human complement (rSBA/hSBA, cut-offs 1:8) 5 y after a single dose of meningococcal serogroups A, C, W, Y tetanus toxoid conjugate vaccine (MenACWY-TT) compared with age-appropriate control vaccines in toddlers and children (NCT00427908). Children were previously randomized (3:1) to receive either MenACWY-TT or control vaccine (MenC-CRM197 in 1-<2 y olds; MenACWY-polysaccharide vaccine [Men-PS] in 2-<11 y olds). Subjects with rSBA-MenC titers <1:8 at any time point were revaccinated with MenC conjugate vaccine and discontinued from the study. A repeated measurement statistical model assessed potential selection effects due to drop-outs. At year 5 in MenACWY-TT-vaccinated-toddlers for serogroups A, C, W, and Y respectively, percentages with rSBA titers ≥1:8 were 73.5%, 77.6%, 34.7%, and 42.9%, hSBA ≥1:8 were 35.6%, 91.7%, 82.6% and 80.0%. For MenC-CRM197 recipients, 63.6% had persisting rSBA-MenC titers ≥1:8 and 90.9% had hSBA-MenC ≥1:8 (not significantly different versus MenACWY-TT for either assay: exploratory analyses). In 2-<11 y olds rSBA titers ≥1:8 in MenACWY-TT-vaccinees were 90.8%, 90.8%, 78.6%, and 78.6% and 15.4%, 100%, 0.0%, 7.7% in Men-PS-vaccinees (significantly different for serogroups A, W and Y, exploratory analyses). Serogroups A, W and Y rSBA GMTs were ≥ 26-fold higher in MenACWY-TT-vaccinees. As expected, GMTs modeled at year 5 to assess the impact of subject drop out (mainly for revaccination), appeared lower for serogroup C. No vaccine-related SAEs were reported. Antibody persistence was observed for all serogroups up to 5 y after MenACWY-TT vaccination.